Chemical incorporation of thioxanthone into β-cyclodextrin and its use in aqueous photopolymerization of methyl methacrylate - Balta, Demet Karaca; Bagdatli, Emine; Arsu, Nergis; Ocal, Nuket; Yagci, Yusuf (ELSEVIER SCIENCE SA, 2008)
Photoinitiated free radical polymerization of methyl methacrylate(MMA) inaqueous solution via hydrogen abstraction mechanism was described. For this purpose, thioxanthone (TX) chromophoric group was chemically incorporated into beta-cyclodextrin (beta-CD) by a simple esterification process. The resulting thioxanthone photoinitiator (TX-beta-CD) exhibited similar spectral characteristics and photoactivity to that of the parent TX molecule. Host guest complexes of MMA with TX-beta-CD in water, in the presence of N-methyldiethanol amine (NMDEA) as a hydrogen donor, facilitated photoinitiated free radical polymerization in aqueous medium. The postulated mechanism is based on the intermolecular reaction of photoexcited triplet TX moiety of TX-beta-CD with NMDEA. The resulting amino alkyl radicals initiate the polymerization. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: photopolymerization; thioxanthone; cyclodextrin; host guest complexes; aqueous polymerization; FREE-RADICAL POLYMERIZATION; HOST/GUEST COMPLEX; INITIATION; SYSTEMS; Chemistry